Life cycle assessment of lattice structures: Balancing mass saving and productivity - Giulia Colombini; Roberto Rosa; Anna Maria Ferrari; Silvio Defanti; Elena Bassoli (Journal of Cleaner Production, 2024)

The relation between sarcomere energetics and the rate of isometric tension relaxation in healthy and diseased cardiac muscle - Giulia Vitale; Cecilia Ferrantini; Nicoletta Piroddi; Beatrice Scellini; Josè Manuel Pioner; Barbara Colombini; Chiara Tesi; Corrado Poggesi (Journal of Muscle Research and Cell Motility, 2021)
Full muscle relaxation happens when [Ca 2+ ] falls below the threshold for force activation. Several experimental models, from whole muscle organs and intact muscle down to skinned fibers, have been used to explore the cascade of kinetic events leading to mechanical relaxation. The use of single myofibrils together with fast solution switching techniques, has provided new information about the role of cross-bridge (CB) dissociation in the time course of isometric force decay. Myofibril’s relaxation is biphasic starting with a slow seemingly linear phase, with a rate constant, slow k REL , followed by a fast mono-exponential phase. Sarcomeres remain isometric during the slow force decay that reflects CB detachment under isometric conditions while the final fast relaxation phase begins with a sudden give of few sarcomeres and is then dominated by intersarcomere dynamics. Based on a simple two-state model of the CB cycle, myofibril slow k REL represents the apparent forward rate with which CBs leave force generating states ( g app ) under isometric conditions and correlates with the energy cost of tension generation (ATPase/tension ratio); in short slow k REL ~ g app ~ tension cost. The validation of this relationship is obtained by simultaneously measuring maximal isometric force and ATP consumption in skinned myocardial strips that provide an unambiguous determination of the relation between contractile and energetic properties of the sarcomere. Thus, combining kinetic experiments in isolated myofibrils and mechanical and energetic measurements in multicellular cardiac strips, we are able to provide direct evidence for a positive linear correlation between myofibril isometric relaxation kinetics (slow k REL ) and the energy cost of force production both measured in preparations from the same cardiac sample. This correlation remains true among different types of muscles with different ATPase activities and also when CB kinetics are altered by cardiomyopathy-related mutations. Sarcomeric mutations associated to hypertrophic cardiomyopathy (HCM), a primary cardiac disorder caused by mutations in genes encoding sarcomeric proteins, have been often found to accelerate CB turnover rate and increase the energy cost of myocardial contraction. Here we review data showing that faster CB detachment results in a proportional increase in the energetic cost of tension generation in heart samples from both HCM patients and mouse models of the disease.

Mechanical properties of intact single fibres from wild-type and MLC/mIgf-1 transgenic mouse muscle - Barbara Colombini; Giulia Benelli; Marta Nocella; Antonio Musarò; Giovanni Cecchi; M. Angela Bagni (Journal of Muscle Research and Cell Motility, 2009)